The Community Rural Tourism and the Happiness of Tourists Visiting Amantani - Barrientos Paredes, Katia Natalia; Vera del Carpio, Maria del Rosario; Yucra Mamani, Yudi Janeh (Street Art & Urban Creativity, 2025)
Currently, rural community tourism stands out as one of the most practiced activities on the island of Amantani, Puno. Among its benefits for the hosts can be recognized the generation of new sources of work, as well as the dissemination of ancestral culture. On the visitors’ side, an experience is identified that leads to a state of happiness. The present study on rural community tourism and happiness aims to determine to what extent this type of tourism influences the happiness of tourists who visit Amantani Island, Puno. A qualitative methodology was used, with a descriptive design. The opinions of tourists who visited the island of Amantani, Puno were collected through interviews and consultation with the Tripadvisor portal, which measures the level of satisfaction of tourists in tourist destinations in Peru. The results concluded that community-based rural tourism positively influences the experience of visiting Amantani Island, Puno, on the levels of positive emotions, commitment, positive relationships, meaning of life and achievement.